Mechanical Properties of Concrete with Recycled Aggregate - Roslina, Omar; Mohd Khairul Ikhwan, Abd Raof; Nor Ashikin, Muhamad Khairussaleh; Ezahtul Shahreen, Ab Wahab (Penerbit UMP, 2011)
In this study, the idea of using waste product is done by recycling the concrete coarse aggregate (RCCA) as a replacement material for normal coarse aggregate. The objective of this study concentrates on mechanical properties that are compressive and flexural strength of concrete with RCCA. 50% and 100% of RCCA were used to replace the normal coarse aggregate and tested on 7, 14 and 28 days age of concrete. The strength of normal concrete as control mix has been compared with the concrete with RCCA. The result revealed that the normal concrete present the highest compressive and flexural strength and followed by concrete with 100% and 50% RCCA. As a conclusion, RCCA reduced the compressive and flexural strength of concrete but still achieve targeted strength for concrete used in construction.